Identification and genetic analysis of major gene ST3GAL4 related to serum alkaline phosphatase in chicken. (February 2023) - Tang, Hehe; Ma, Yanchao; Li, Jianzeng; Zhang, Zhenzhen; Li, Wenting; Cai, Chunxia; Zhang, Lujie; Li, Zhuanjian; Tian, Yadong; Zhang, Yanhua; Ji, Jinqing; Han, Lu; et al.
Abstract: Alkaline phosphatase (ALP) is a marker of osteoblast maturation and an important indicator of bone metabolism. The activity of ALP can reflect the bone metabolism and growth traits of animals, so the polymorphism affecting ALP expression deserves further study. In this study, we identified an SNP site in ST3GAL4 found by genome-wide association studies (GWAS) in previous studies, 8 SNPs were also identified by DNA sequencing. Interestingly, there were 4 SNPs (rs475471G > A, rs475533C > T, rs475621A > G, rs475647C > A) completely linked by haplotype analysis. Therefore, we selected a tag SNP rs475471G > A to further analyze the ALP level of different genotypes in Hubbard leg disease population and an F2 chicken resource population produced by Anka and Gushi chickens and carried out population genetic analysis in 18 chicken breeds. Association analysis showed that this QTL within ST3GAL4 was highly correlated with ALP level. The mutant individuals with genotype AA had the highest ALP level, followed by GA and GG carriers. The mutant individual carriers of AA and GA genotype had higher values for body weight (BW), chest width (CW), body slanting length (BSL), pelvis width (PW) at 4-week, the semi-evisceration weight (SEW), evisceration weight (EW) and Leg weight (LW) than GG genotypes. The amplification and typing of 4852 DNA samples from 18 different breeds showed GG genotype mainly existed in egg-type chickens and dual-type chickens, while the AA genotype was mainly distributed in commercial broilers and F2 resource population. The individual carriers of the AA genotype had the highest ALP and showed better growth performance. Besides, tissue expression analysis used Cobb broiler showed significant differences between different genotypes in the spleen and duodenum. Taken together, this was the first time to determine 9 SNPs within ST3GAL4 related to ALP in chickens, 4 of them were complete linkage with each other, which provides useful information on the mutation of ST3GAL4 and could predict the serum ALP level of chicken early and as an effective potential molecular breeding marker for chickens. Highlights: First time determined 9 SNPs within ST3GAL4 were related to ALP in chickens, 4 of them were complete linkage sequence variants. Through the analysis of the association results of Hubbard population and F2 resource population, we determined that ST3GAL4 is a major gene related to ALP. In conclusion, our study first time to report the causal variant of chicken serum ALP level and can be used as a molecular marker for genetic improvement of chicken breeds. This study might also provide a reference for future studies of molecular mechanism about ST3GAL4 gene.